2011
DOI: 10.1021/jf201342t
|View full text |Cite
|
Sign up to set email alerts
|

Residue Potential of Norsesquiterpene Glycosides in Tissues of Cattle Fed Austral Bracken (Pteridium esculentum)

Abstract: Austral bracken, Pteridium esculentum , occurs widely in Australian grazing lands and contains both the known carcinogen ptaquiloside and its hydroxy analogue, ptesculentoside, with untested carcinogenic potential. Calves were fed a diet containing 19% P. esculentum that delivered 1.8 mg of ptaquiloside and 4.0 mg of ptesculentoside per kilogram of body weight (bw) per day to explore the carcass residue potential of these compounds. Concentrations of ptaquiloside and ptesculentoside in the liver, kidney, skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 9 publications
0
34
0
2
Order By: Relevance
“…Bovinos que consomem Pteridium spp. apresentam resíduos de ptaquilo-sídeo, uma substância cancerígena presente nessa planta (Hirono et al 1984), no leite e na carne, em quantidades variáveis (Alonso-Amelot et al 1996, 1998, Fletcher et al 2011, Calderón et al 2013. Embora o efeito carcinogênico da ingestão deste cancerígeno por humanos, juntamente com o leite ou carne contaminados, não seja confirmado, alguns autores acreditam que exista uma relação entre a incidência de neoplasias gástricas em humanos e a ingestão de ptaquilosídeo em regiões invadidas por Pteridium spp.…”
Section: Discussionunclassified
“…Bovinos que consomem Pteridium spp. apresentam resíduos de ptaquilo-sídeo, uma substância cancerígena presente nessa planta (Hirono et al 1984), no leite e na carne, em quantidades variáveis (Alonso-Amelot et al 1996, 1998, Fletcher et al 2011, Calderón et al 2013. Embora o efeito carcinogênico da ingestão deste cancerígeno por humanos, juntamente com o leite ou carne contaminados, não seja confirmado, alguns autores acreditam que exista uma relação entre a incidência de neoplasias gástricas em humanos e a ingestão de ptaquilosídeo em regiões invadidas por Pteridium spp.…”
Section: Discussionunclassified
“…The mutagenicity, clastogenicity, teratogenicity and carcinogenicity have been demonstrated. Some epidemiological evidences have shown higher risk of gastric and/or esophageal cancer in people who consume bracken crosiers; people who consume milk of cows that are grazing in brackeninfested areas (Yamada et al, 2007;Cot, 2008;Fletcher et al, 2011). PT has been found in milk of bracken-fed cattle through experimental tests.…”
Section: Motahhareh Tourchi-roudsarimentioning
confidence: 99%
“…The studies show that even the activity of carcinogenic compounds in the milk of animals fed on bracken is more than bracken compounds (Alonso-Amelot et al, 1996). Recently, Ptaquiloside has been detected in meat and milk from cattle consuming bracken (Bonadies et al, 2010;Fletcher et al, 2011). Pasteurisation was found to decrease ptaquiloside concentrations in milk by 50% and a 75% decrease by boiling (Villalobos-Salazar et al, 2000).…”
Section: Milkmentioning
confidence: 99%
“…This fern is also well established as a carcinogen in humans and livestock through ingestion of plant crosiers (Abnet, 2007;Gil da Costa et al, 2012;Sugimura, 2000). Humans can be exposed to the plant indirectly through consumption of milk and meat from animals grazing on bracken fern (Alonso-Amelot & Avendano, 2002;Fletcher et al, 2011;Shahin et al, 1999) or through ingestion of contaminated water (Rasmussen et al, 2003). Previous studies conducted in this laboratory have also demonstrated (in mice) that ptaquiloside produces immunosuppressive effects, including direct toxic effects on NK cells (Latorre et al, 2009).…”
Section: Introductionmentioning
confidence: 97%